RETRACTED: HOXC10 Promotes the Metastasis of Human Lung Adenocarcinoma and Indicates Poor Survival Outcome - Tang, Xiao-Lei; Ding, Bang-Xian; Hua, Ying; Chen, Hao; Wu, Tao; Chen, Zhang-Quan; Yuan, Chun-Hui (Frontiers in Physiology, 2017)
Background: As master regulator of embryonic morphogenesis, homeodomain-containing gene 10 (HOXC10) has been found to promote progression of human cancers and indicates poor survival outcome. However, the role of HOXC10 in lung adenocarcinoma still unclear. Methods: HOXC10 expression was evaluated in 63 primary lung adenocarcinoma tissues from our local hospital, and further systematically confirmed in lung cancer tissues from six GEO datasets (GSE19188, GSE31210, GSE10072, GSE7670, GSE32863, GSE30219) and Kaplan-Meier plotter database. The role of HOXC10 in lung cancer metastasis was further validated by cellular and molecular studies. Results: the expression of HOXC10 was significantly increased in human lung adenocarcinoma samples from Wuhu No.2 People’s Hospital, about 4.219 times compared with normal tissues, and significantly correlated with TNM stage, lymph node and distal metastasis. Upregulation of HOXC10 indicated a poor overall/relapse free survival of lung cancer patients from Wuhu No.2 People’s Hospital, GEO datasets and Kaplan-Meier plotter database, especially in patients with lung adenocarcinoma. Knockdown or ectopic expression assays confirmed that HOXC10 enhanced the phosphorylation of PI3K, regulated the expression of epithelial-to-mesenchymal transition (EMT) markers: MMP2/9, VCAM-1, vimentin and E-cadherin. Cellular study further confirmed that HOXC10 was required for migration, invasion and adhesion of lung cancer cells. Conclusion: These findings suggest that HOXC10 plays a pivotal role in the metastasis of human lung cancer and highlight its usefulness as a potential prognostic marker or therapeutic target in human lung adenocarcinoma.